1. Immunohistochemical Study of the Immunoreactive Follicle Stimulating Hormone (ir-FSH) Cells Distribution in Pituitary Gland of Rat(Rattus norvegicus) - Patrick Flaggellata; Sri Wahyuni; Muhammad Jalaluddin; Hamny Hamny; Gholib Gholib; T. Armansyah, TR; Muslim Akmal (Jurnal Medika Veterinaria, 2018)
The objective of this study was to identified the development of the immunoreactive follicle stimulating hormone (ir-FSH) cells in pituitary glands of rats (Rattus norvegicus)in different age using immunohistochemical (IHC) methods. The pituitary organ that used in this study was collected from eight white female rats aged 2, 4, 6, and 12 months. Pituitary glands were processed histologically and stained with IHC methods to detect the ir-FSH cells. The result showed that the ir-FSH cells were observed in pars distalis (PD), pars tuberalis (PT), and pars intermedia (PI) of adenohypophysis with different number of cells. Furthermore, ir-FSH cells were found abundantly (+++) in the PT and a few (+) in PD of rats aged two months. In rats aged 4 months those cells were distributed in slight number (+) in PT and abundant (+++) in PD. In addition, the cells were also found in a great quantities in rats whose ages were 6 months, (+++) in both PT and PD, but these cells decreased (++) in rats aged 12 months in PD and absent (-) in PT. In conclusion, the devalopment and distribution of ir-FSH cells were found in pars tuberalis and pars distalis adenohypophysis in the pituitary glands of rats aged 2 up to 12 months with different number and distribution patterns.